2024
DOI: 10.1186/s12884-023-06189-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in utilization and provisioning of obstetric care services (OCS) in India: a mixed-methods systematic review

Sushmita Singh,
Rahul Rajak

Abstract: Background Despite the reduction in the maternal mortality ratio, barriers in obstetric care services (OCS) remain a significant risk factor for adverse maternal and perinatal outcomes in India. This review covers the ‘continuum of care’ (ANC, child delivery, and PNC services) and identifies multiple barriers in provisioning as well as utilization of OCS in India. We conducted a systematic review to understand the barriers using a mixed-methods approach. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This finding aligns with earlier studies that have recognized economic hardships as a major obstacle in obtaining maternal healthcare in low- and middle-income nations [ 51 , 55 ], a study in Bangladesh, found that financial constraints significantly influenced the decision to seek maternal health services, with many women unable to afford the costs associated with healthcare visits, medications, and necessary tests [ 56 ], a study in India, found that financial limitations were a critical barrier to maternal health service utilization. Women from poorer households were less likely to access institutional deliveries and postnatal care due to the costs associated with these services [ 57 ], a study in Uganda highlighted that economic hardship was a major factor affecting maternal health service utilization [ 58 ], and research in Pakistan also demonstrated that financial barriers were a major obstacle to accessing maternal health services [ 59 ]. Improving access to maternal healthcare services requires addressing these barriers and empowering women through education and equitable healthcare access.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with earlier studies that have recognized economic hardships as a major obstacle in obtaining maternal healthcare in low- and middle-income nations [ 51 , 55 ], a study in Bangladesh, found that financial constraints significantly influenced the decision to seek maternal health services, with many women unable to afford the costs associated with healthcare visits, medications, and necessary tests [ 56 ], a study in India, found that financial limitations were a critical barrier to maternal health service utilization. Women from poorer households were less likely to access institutional deliveries and postnatal care due to the costs associated with these services [ 57 ], a study in Uganda highlighted that economic hardship was a major factor affecting maternal health service utilization [ 58 ], and research in Pakistan also demonstrated that financial barriers were a major obstacle to accessing maternal health services [ 59 ]. Improving access to maternal healthcare services requires addressing these barriers and empowering women through education and equitable healthcare access.…”
Section: Discussionmentioning
confidence: 99%